An update of medical care in Marfan syndrome - Hsin-Hui Chiu (Tzu Chi Medical Journal)
Marfan syndrome (MFS), a multisystemic connective disorder, caused by fibrillin 1 gene mutations with autosomal dominant inheritance. The disease spectrum is wide and the major causes of death are related to aortic root aneurysm or dissection. The purposes of medical treatment are to reduce structural changes in the aortic wall and slow aortic root dilatation. Advance in medical researches have provided new insights into the pathogenesis of disease and opened up new horizons for treatments. Several medications such as angiotensin II type I receptor blockers, β-blockers, angiotensin-converting enzyme inhibitors, calcium channel blockers, tetracyclines, and statins have been studied for the purpose. Currently, the life expectancy of Marfan patients improves significantly and is closes to the general population with proper treatment. In this article, we review and update the medical treatments for patients with MFS.